Schiff base-functionalized silatrane-based receptor as a potential chemo-sensor for the detection of Al3+ ions. (15th April 2021) - Singh, Gurjaspreet; Priyanka,; Singh, Akshpreeet; Satija, Pinky; Sushma,; Pawan,; Mohit,; Singh, Jandeep; Singh, Jasbhinder
Abstract : Excess Al 3+ ions are considered toxic to living organisms. Abstract : Excess Al 3+ ions are considered toxic to living organisms. Keeping the harmful effects of excess Al 3+ metal ions in mind, a new Schiff base = functionalized silatrane as a potential chemo-sensor for the recognition of aluminium metal ions with high selectivity and specificity has been designed and well characterized using various characterization techniques such as IR, 1 H NMR, 13 C NMR, TGA, and mass spectroscopy. The chemo-sensing properties were studied using ultraviolet and fluorescence spectroscopy. The absorption spectrum of the synthesized receptor was changed only by the addition of Al 3+ ions, while other ions showed negligible changes. The 1 : 1 stoichiometric ratio of the chemo-sensor 4b with Al 3+ was confirmed by Job's plot and linearity in the B–H plot. The limit of detection observed for Al 3+ ions was 2.273 × 10 −7 M and 9.8 × 10 −9 M from ultraviolet and fluorescence spectroscopy, respectively. The binding constant from the B–H plot and the Stern–Volmer quenching constant were found to be 0.2279 × 10 6 M −1 and 2.7 × 10 6 M −1, respectively. These results explain the potential chemo-selectivity of the receptor 4b towards Al 3+ metal ions, which may be useful for biological and industrial purposes.